THE EFFECT OF TEACHER COMPETENCY DEVELOPMENT MANAGEMENT AND WORK ATTITUDE ON TEACHER PERFORMANCE AT PUBLIC JUNIOR HIGH SCHOOLS IN THE PENUKAL UTARA DISTRICT - Naila Putri Imani; Karoma Karoma; Asri Karolina (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effect of professional competency development management and work attitude on teacher performance at public junior high schools in North Penukal District, both partially and simultaneously. This research uses a quantitative approach with a survey method. The research sample used a saturated sampling technique, in which the entire population of teachers was used as the research sample. Data collection was carried out through questionnaires prepared based on indicators of the research variables and supported by documentation. The data analysis techniques used included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing using the t-test and F-test with a significance level of 5%. The results showed that partially the management of professional competency development had a positive but not significant effect on teacher performance. Meanwhile, work attitude had a positive and significant effect on teacher performance. Simultaneously, the management of professional competency development and work attitude had a significant effect on teacher performance. This indicates that improving work attitudes and managing professional competency development effectively can enhance teacher performance optimally.